Обробка газорідинних систем на трубчастих решітках із стабілізатором пінного шару - Моїсєєв, Віктор Федорович; Манойло, Євгенія Володимирівна; Васильєв, Михайло Ілліч; Репко, Каліф Юрійович; Давидов, Денис Валерійович (НТУ "ХПІ", 2017)
Промислова реалізація методу стабілізації газорідинного шару дозволяє значно розширити галузь застосування пінних апаратів і відкриває нові можливості інтенсифікації технологічних процесів з одночасним створенням маловідхідних технологій. У статті встановлені основні параметри, що впливають на гідродинаміку трубчастих решіток із стабілізатором піни і без нього. Виявлено зв'язок гідродинамічних параметрів. Отримані залежності точніше характеризують гідродинамічну обстановку в апараті. Наводиться вплив наявності стабілізатора на характеристики динамічного двухфазного шару. Розглянуто гідродинамічні закономірності пінного шару на трубчастих решітках зі стабілізатором піни і його вплив на роботу апарата. Показано, що використання стабілізатора знижує бризковіднесення, а також збільшує ефективність виділення з газів компонентів, які важко уловити.

The article is devoted to the study of hydrodynamic parameters in the processing of gas-liquid systems with stabilization of foam layer. The problem of processing industrial gas streams is solved by conducting the process in an intensive mode. The industrial realization of a method of stabilization of gas liquid bed allows considerably to expand a field of application of frothy apparatuses and opens out new capabilities of an intensification of technological processes with simultaneous making of lowwaste technologies. In the article the fundamental parameters influencing to hydrodynamics of tubular gratings with the stabilizing of foam and without it are highlighted. The connection of hydrodynamic quantities is revealed. The received relations characterize hydrodynamic conditions in the apparatus more precisely. The relations of gas content to a density of forced-circulation and velocity of gas, and also influence of availability of the stabilizing agent to performances of dynamical two-phase bed are resulted. Is considered sparks ablation on tubular gratings with the stabilizing of foam and its influence to activity of the apparatus. Thus, the main result of the work is to update the technology of gas cleaning by the reduction of sparks ablation. It is reached by application of the padding stabilizing, which besides augments efficiency of separation from gases difficultly trapped components. The article establishes the basic parameters influencing the hydrodynamics of tubular lattices with and without a foam stabilizer. The connection of hydrodynamic parameters is revealed. The obtained dependencies more precisely characterize the hydrodynamic situation in the apparatus.
Processing of gas-liquid systems on tubular gratings with stabilizer of a foam layer
Keywords: викиди промислові; викиди газові; уловлювання; гідродинаміка; масообмін; очищення; стабілізація; industrial gas emissions; catching process; hydrodynamics; mass transfer; foam apparatus; clearing; stabilization